A good night's sleep - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
Everyday experiences can present major marketing opportunities. This case study provides an overview of the marketing possibilities that emerge from international cultural differences in sleep habits and patterns. The Japanese market is of particular interest, due to a unique type of bed comprised of a number of elements, each designed for optimum sleep quality.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). A Good Night's Sleep. In International marketing (pp. 227-228). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Export marketing -- Case studies; Beds -- Japan -- Design